Analisis Akad Pembiayaan Qardh dalam Lembaga Keuangan Mikro Syariah Daerah Istimewa Yogyakarta - Muhammad Ash Shiddiqy (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2019)
This study aims to find out how the implementation of the qardh contract in the Almuna Sharia Microfinance Institutions Blessing Mandiri Special Region of Yogyakarta. This study uses an empirical juridical method. Empirical juridical research is used to analyze various regulations regarding qardh financing contracts in Islamic Microfinance Institutions (LKMS) and to analyze applicable laws of community behavior in their lives. The type of data and materials of this study come from primary data and secondary data. Primary data comes from the results of interviews and secondary data derived from literature. The collection technique in this study was conducted by interviewing respondents to get the right and reliable information. The analysis technique used in this research is descriptive method with a qualitative approach.This study found findings, namely financing products carried out at LKMS Almuna Mandiri Blessings, among others, namely Qardh (borrowing virtue). The qardh contract implemented at LKMS Almuna Berkah Mandiri is in accordance with sharia principles. This qardh agreement is intended for LKMS Almuna Berkah Mandiri customers who have small businesses but are not economically capable and want to expand their business. The LKMS Almuna Berkah Mandiri program fund comes from LAZNAS BSM Umat. The amount of qardh financing granted by LKMS Almuna Berkah Mandiri is Rp. 1,000,000.00 (one million rupiah) with a period of 50 (fifty) weeks or equivalent to 1 (one) year over 2 (two) weeks. The qardh installment payment is made after 1 (one) week after the disbursement of funds.